Decarbonization Measures: A Real Effect or Just a Declaration? An Assessment of Oil and Gas Companies’ Progress towards Carbon Neutrality - Alina Cherepovitsyna; Nadezhda Sheveleva; Arina Riadinskaia; Konstantin Danilin (Energies, 2023)
Efforts to control climate change with the aim of achieving carbon neutrality by 2050 have had the most significant impact on businesses operating in the energy sector, which produce large amounts of greenhouse gas (GHG) emissions. In light of such policies, oil and gas companies have set goals aimed at reducing GHG emissions and achieving carbon neutrality, but the issue remains open as to how such activities and progress towards these goals can be evaluated. This study attempts to assess the activities and progress of oil and gas companies towards carbon neutrality, with a focus on quantitative evaluation of goal achievement. First, an algorithm was developed for selecting global oil and gas companies for the analysis that reported their activities in 2022. Using this algorithm, a list of companies was compiled and their goals with regard to carbon neutrality were analyzed. Second, an assessment of how information is presented in corporate reports and which activities aimed at achieving carbon neutrality are reflected there was performed using the proposed checklist. Third, a method for evaluating the progress of oil and gas companies towards intermediate goals in the area of carbon neutrality was developed and tested. The method is based on assessing and comparing trends for oil and gas companies aiming to achieve intermediate goals in reducing carbon intensity. As a result, companies were classified into three categories: (1) those showing carbon neutrality achievement rates exceeding the expected average annual rates, (2) those with fixed carbon neutrality achievement rates below the expected average annual rates, and (3) those demonstrating no movement towards intermediate goals or a negative trend. The main methods used in this study included content analysis, checklist development, decomposition, critical and comparative analysis, and simple statistical methods.